Relationship between First Calving Friesian Holstein Age and Days Open With Milk Production of Dairy Cows FH on Second And Third Lactation in BPPIB TSP Bunikasih Cianjur - Khaerun Nissa Suci A’ini; Dudi Dudi; Raden Febrianto Christi (JURNAL ILMIAH PETERNAKAN TERPADU, 2021)
The purpose of this research was to know the performance and relationship between age at first calving and days open with the production of dairy milk FH on second and third lactation. The research was started on the first week to the second week of October 2020 in BPPIB TSP Bunikasih Cianjur West Java. The study used correlational methods and data analysis using multiple linears. The results showed that the age of the first child and days open with milk production of dairy cows FH on second and third lactation in BPPIB TSP Bunikasih Cianjur West Java has a correlation of 0,029 and -0,316 included low categories. The model of alleged regression equation for second lactation is 6231,29 – 798,66 X1 + 4,54 X2 with a value of R = 6,6%. The model of alleged regression equation for third lactation is  1729,59 + 31,321 X1+ 15,491 X2 with a value of R = 35,1% and standard errors are 3,71 and 3,41, respectively. It was concluded that milk production in BPPIB TSP Bunikasih Cianjur was more than 64 percent influenced by other factors beyond the age factor of the first child and days open of FH cows.